The Effect of Dividen Policy, Capital Structure, and Retained Earnings on The Capital Adequacy Ratio on Multifinance Companies That Go Public In 2020–2025: A Systematic Literature Review - Giovani Huiser Mangalindung; Supardi Tahir (Dinasti Accounting Review, 2026)
The purpose of this study is to analyze the influence of dividend policy, capital structure, and retained earnings on the Capital Adequacy Ratio (CAR) for multifinance companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2025 timeframe. The research employs the methodology of Systematic Literature Review (SLR) with a quantitative approach based on literature collected. To ensure the relevance and authenticity of the sources, the PRISMA approach has identified 12 national and international journal publications. The results indicate that the dividend policy, as measured by the Dividend Payout Ratio (DPR), has a significant negative influence on CAR because paying dividends reduces the internal equity available for strengthening capital. The capital structure as measured by the debt to equity ratio (DER) harms CAR. The higher the level of debt, the greater the financial risk for companies that use financing. On the other hand, the impact of retained earnings on CAR is positive and statistically significant given that undistributed gains are improving the components of equity and increasing the ability to absorb risk. The novelty of this work is the integrative synthesis of these three factors at the same time in the context of post-pandemic publicly listed multi-finance companies, which are not commonly examined in the present literature. These results are relevant for the management of multi-finance companies and for the regulators in establishing sustainable capital restrictions.